2006
DOI: 10.2486/indhealth.44.123
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Low Back Pain among Staffs in Schools for Physically and Mentally Handicapped Children

Abstract: The objective of this study is to clarify the prevalence of and risk factors for low back pain (LBP) in schools for physically and mentally handicapped children. This study design is a cross-sectional study. The subjects included were 1,869 staff members from 19 prefectural schools for children in Shizuoka Prefecture, Japan, which included schools for the blind, deaf-mutes, physically handicapped, and mentally retarded children. A total of 975 subjects completed two postal questionnaires which included morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 14 publications
4
41
1
Order By: Relevance
“…On the other hand however, other research has suggested that LBP is not related to hormonal fluctuations during the menstrual cycle nor to the use of Oral Contraceptives (OC) 14) . Back pain is known to be an increasingly common problem for the Japanese workforce 15) and has been studied epidemiologically in a variety of occupational fields such as construction workers 16) , taxi drivers 17) and school personnel [18][19][20] . The Japanese health care workforce is also known to suffer LBP, with previous research revealing high rates of musculoskeletal disorders among hospital nurses 6,8,21) and nursing home workers [22][23][24] .…”
mentioning
confidence: 99%
“…On the other hand however, other research has suggested that LBP is not related to hormonal fluctuations during the menstrual cycle nor to the use of Oral Contraceptives (OC) 14) . Back pain is known to be an increasingly common problem for the Japanese workforce 15) and has been studied epidemiologically in a variety of occupational fields such as construction workers 16) , taxi drivers 17) and school personnel [18][19][20] . The Japanese health care workforce is also known to suffer LBP, with previous research revealing high rates of musculoskeletal disorders among hospital nurses 6,8,21) and nursing home workers [22][23][24] .…”
mentioning
confidence: 99%
“…Although the response rate of about 60% is comparable to other studies for this type of school 29,30) , serious selection bias due to nonresponse of a substantial number of teachers/educational staff cannot be dismissed easily. A further limitation consists of the possibility of recall bias due to the retrospective design of our study.…”
Section: Limitationsmentioning
confidence: 64%
“…Most of the staff in our study were teachers 1) . Most teachers in such schools were not only teaching but also engaged in nursing activity 1) . However, we have not yet clarified levels of job stressors and job stress among teachers engaged in nursing activity.…”
Section: Introductionmentioning
confidence: 99%
“…We reported an association between low back pain and several job stressors among staff members in schools for handicapped children 1) . Most of the staff in our study were teachers 1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation